ANALISIS GAYA KEPEMIMPINAN MOHAMMAD IDRIS ABDUL SHOMAD SEBAGAI WALIKOTA DEPOK DALAM PENANGANAN PANDEMI - Sri Mulyani (2022)
Mohammad Idris, who serves as mayor of Depok, is one of the regional heads whose leadership is quite controversial in the community because of several policies that have been made. The city of Depok, which is one of the supporting cities for the capital, has become a city that has various city problems that require the right leadership to deal with existing problems. In 2020 Depok will also become the first city of the Covid-19 cluster in Indonesia, which of course poses new challenges for the leadership of regional heads. This study aims to describe the leadership style possessed by Mohammad Idris as the mayor of Depok in handling the Covid-19 pandemic by using the theory of leadership concepts and leadership styles according to Ralph White & Ronald Lippit. The method used in this research is descriptive qualitative using primary data sources and secondary data. Data collection techniques were carried out by means of in-depth interviews. This study uses three stages of data analysis after data collection, namely data reduction, data presentation, and conclusion drawing/verification. And the results of this study indicate that there is a tendency of authoritarian leadership style and religious leadership that is owned by Mohammad Idris as mayor of Depok. However, this authoritarian style was not maximized in handling the Covid-19 pandemic.